Buckling of imperfect cone-cylinder transition subjected to external pressure. (November 2020) - Ismail, M.S.; Ifayefunmi, O.; Fadzullah, S.H.S.M.; Johar, M.
Abstract: The paper presents a result of the numerical investigation into the buckling behaviour of geometrically imperfect cone-cylinder transition subjected to external pressure. The models are assumed to be made from the Hiduminium alloy (HE-15). Various initial geometric imperfections such as eigenmode imperfection and Single Load Indentation (SLI) imperfections were superimposed on the perfect cone-cylinder shell. The reduction of the buckling strength was then quantified numerically. As expected, the buckling strength of cone-cylinder shells were strongly affected by initial geometric imperfection and the reduction in buckling strength was seen to be strongly dependent on the choice and location of imperfection. Overall, the lowest SLI imperfection curve produces the worst sensitivity as compared to the eigenmode imperfection curve. Conservative knockdown factors that can be implemented for the design of cone-cylinder transition have been proposed for both eigenmode imperfection and SLI imperfection. Finally, a simple empirical solution based on several case studies has been proposed that could reasonably be used to estimate the buckling of externally pressurized cone-cylinder shell transition under Geometrical and Materially Non-linear Analysis (GMNA) and Geometrical and Materially Non-linear Imperfection Analysis (GMNIA) cases. A good correlation with the ultimate strength is observed with the application of the proposed empirical formula. Highlights: First Numerical prediction into buckling behaviour of imperfect cone-cylinder transition subjected to external pressure. Comparison of results show that single load indentation imperfection is more detrimental compared to Eigenmode imperfection. Proposed knockdown factor for both Eigenmode imperfection and single load indentation imperfection for design purposes.